2011
DOI: 10.1613/jair.3213
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent Learning in Large Anonymous Games

Abstract: In large systems, it is important for agents to learn to act effectively, but sophisticated multi-agent learning algorithms generally do not scale. An alternative approach is to find restricted classes of games where simple, efficient algorithms converge. It is shown that stage learning efficiently converges to Nash equilibria in large anonymous games if bestreply dynamics converge. Two features are identified that improve convergence. First, rather than making learning more difficult, more agents are actually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Any λ-Lipschitz k-strategy anonymous game is guaranteed to have an ǫ-approximate pure Nash equilibrium, with ǫ = O(λk) [2,15]. The convergence rate to a Nash equilibrium of best-reply dynamics in the context of two-strategy Lipschitz anonymous games is studied by [3,24]. Moreover, [5] showed that finding a pure equilibrium in anonymous games is easy if the number of strategies is constant w.r.t.…”
Section: Related Workmentioning
confidence: 99%
“…Any λ-Lipschitz k-strategy anonymous game is guaranteed to have an ǫ-approximate pure Nash equilibrium, with ǫ = O(λk) [2,15]. The convergence rate to a Nash equilibrium of best-reply dynamics in the context of two-strategy Lipschitz anonymous games is studied by [3,24]. Moreover, [5] showed that finding a pure equilibrium in anonymous games is easy if the number of strategies is constant w.r.t.…”
Section: Related Workmentioning
confidence: 99%
“…Any λ-Lipschitz k-strategy anonymous game is guaranteed to have an ǫ-approximate pure Nash equilibrium, with ǫ = O(λk) [2,15]. The convergence rate to a Nash equilibrium of best-reply dynamics in the context of two-strategy Lipschitz anonymous games is studied by [3,24]. Moreover, [5] showed that finding a pure equilibrium in anonymous games is easy if the number of strategies is constant w.r.t.…”
Section: Related Workmentioning
confidence: 99%
“…"Sink" equilibria are studied in (Goemans et al, 2005, Mirrokni andSkopalik, 2009). 4 This case is studied in Quint et al (1997) for 2-player games and in Kash et al (2011) for anonymous games. 5 There are, of course, many other possible playing sequences.…”
Section: Introductionmentioning
confidence: 99%